Manufacturing method of adhesives, packaging materials, and recycled substrates
A laminating adhesive with a specific polyester polyol and polyisocyanate composition allows for easy separation of sealant base materials from packaging layers in an alkaline solution, addressing the challenge of recycling plastic packaging while preserving adhesive strength and retort resistance.
Patent Information
- Application Number
- JP2020141175
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-31
- Filing Date
- 2020-08-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-08-24
AI Technical Summary
Existing technologies fail to effectively separate the sealant base material from other base materials in laminated packaging materials, which is crucial for recycling plastic packaging materials, while maintaining adhesive strength and retort resistance.
A laminating adhesive containing a polyester polyol component and at least one polyisocyanate component, with an acid value of 5 to 40 mgKOH/g, is used to form a removable adhesive layer that facilitates separation in an alkaline aqueous solution, allowing for easy recovery of the sealant base material.
The adhesive ensures excellent removability of the pattern layer and sealant base material, maintaining adhesive strength and retort resistance, thereby enhancing the recyclability of packaging materials.
Smart Images

Figure 0007615568000001 
Figure 0007615568000002 
Figure 0007615568000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive used to form a removable adhesive layer for recycling a sealant substrate from a packaging material, a packaging material comprising the adhesive, and a method for producing a recycled substrate from the packaging material. [Background technology]
[0002] In recent years, packaging, plastic bottles, and other plastic products made from plastic film have been discarded and dumped in the ocean as garbage, causing environmental pollution. These plastic products break down in seawater and become submicron-sized fragments (microplastics), which float in the seawater. If the plastics are ingested by marine organisms such as fish, they will be concentrated in the organisms' bodies, and there is concern that they will affect the health of seabirds and humans who consume the marine organisms as food. In addition, harmful substances originating from inks, adhesives, and coating layers are attached to the surface of the microplastics generated from the packaging, which is of further concern from the perspective of environmental conservation. In order to improve this problem, various efforts to reduce microplastics have been started.
[0003] The plastic products mainly include food packaging packages using plastic substrates. In these packages, various plastic substrates such as polyester (PET), nylon (NY), and polypropylene (OPP, CPP) substrates are used as film substrates. These plastic substrates are coated with a pattern layer using gravure ink, flexographic ink, or other printing inks, and are then bonded to a sealant substrate via an adhesive or the like to form a laminate. The laminate is then cut and heat-sealed to form a package.
[0004] Attempts to reduce the amount of microplastics in the above-mentioned packaging include (1) replacing the plastic base material with "paper" made from wood, a renewable resource, (2) mono-materializing the plastic base material into a single material (polyolefin) and recycling it, and (3) removing impurities and recycling the plastic base material.
[0005] The above-mentioned (1) is promising in terms of safety and recyclability, but it is inferior in many aspects to conventional plastic substrates in terms of performance, such as gas barrier properties, water vapor barrier properties, and water resistance. Regarding (2) above, technology is being developed to cover the weaknesses of polyolefins with functional coating agents such as barrier coating agents, but since polyolefins are inferior in performance to conventional plastic substrates in terms of retort suitability and light blocking properties, it is not easy to replace them with polyolefins. Furthermore, there is also the issue that inks, functional coating agents, and adhesives between polyolefin substrates become impurities when recycling polyolefins.
[0006] As for the above (3), attempts have been made to remove the pattern layer on the outer surface of the package, which becomes an impurity during the recycling process, with an alkaline aqueous solution. For example, Cited Document 1 discloses a technique in which an undercoat layer made of an acrylic resin or a styrene-maleic acid resin is provided on a plastic substrate, and a printed layer disposed on the undercoat layer is removed with alkaline water. Patent Document 2 discloses a technique in which an ink containing a polyurethane resin or an acrylic resin having an acidic group as a binder resin is printed, and the printed layer is removed with alkaline water. However, these techniques only remove the surface-printed ink on the outside of the package, and do not allow the sealant substrate to be peeled from the other substrates in the laminate.
[0007] In a packaging material in which a substrate including a plastic layer and a printed layer such as a picture layer and a sealant substrate are laminated with an adhesive, a technology for peeling the sealant substrate from the other substrates and recycling the sealant substrate, which is particularly thick and accounts for a large proportion of the entire packaging material, is an important technology that can be used industrially to promote the recycling of plastics and contribute to environmental conservation. However, no technology has yet been reported that combines the required performance of a laminating adhesive with the function of peeling the sealant substrate from the other substrates. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2001-131484 A [Patent Document 2] Japanese Patent Application Publication No. 11-209677 Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, an object of the present invention is to provide an adhesive with excellent releasability that enables a pattern layer or the like to be easily removed from a packaging material to easily recover a sealant substrate, a packaging material comprising the adhesive, and a method for producing a recycled substrate from the packaging material. [Means for solving the problem]
[0010] As a result of extensive research into the above-mentioned problems, the inventors have found that the problems can be solved by using the laminating adhesive described below, and have arrived at the present invention. The present invention relates to the following inventions [1] to
[11] .
[0011] [1] An adhesive that forms a removable adhesive layer constituting a packaging material in which a substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer, and a sealant substrate 2 are laminated in this order from the outside, and the substrate 1 is peeled off to recycle the sealant substrate 2, the adhesive comprising a polyester polyol component and at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and aralkyl polyisocyanates, and the adhesive has an acid value of 5 to 40 mgKOH / g.
[0012] [2] The adhesive according to [1], wherein the polyester polyol component has a number average molecular weight of 5,000 to 15,000.
[0013] [3] The adhesive according to [1] or [2], wherein the acid value of the polyester polyol component is 10 to 40 mgKOH / g.
[0014] [4] The adhesive according to any one of [1] to [3], wherein the polyester polyol component contains an acid anhydride-modified polyester polyurethane polyol.
[0015] [5] The adhesive according to any one of [1] to [4], wherein the polyester polyol component contains a polyester polyol having a number average molecular weight of 5,000 to 15,000 and a polyester polyol having a number average molecular weight of less than 3,000.
[0016] [6] The adhesive according to any one of [1] to [5], further comprising a phosphorus oxyacid or a derivative thereof in an amount of 0.01 to 5 mass % based on the solid content of the adhesive.
[0017] [7] The adhesive according to any one of [1] to [6], further comprising fine particles having an average particle size of 1 to 10 μm.
[0018] [8] The adhesive according to [7], wherein the content of the fine particles is 0.1 to 10 mass % based on the solid content of the adhesive.
[0019] [9] A packaging material having a configuration in which a substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer formed from the adhesive described in any one of [1] to [8], and a sealant substrate 2 are laminated in this order from the outside.
[0020]
[10] The packaging material according to [9], wherein the sealant substrate 2 is a layer formed by extrusion lamination, and the removable adhesive layer has a thickness of 0.01 to 1 μm.
[0021]
[11] A method for producing a recycled substrate, comprising the step of immersing a packaging material in a basic aqueous solution, the packaging material comprising a substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer formed from the adhesive described in any one of [1] to [8], and a sealant substrate 2 laminated in this order from the outside, the basic aqueous solution containing a basic compound in an amount of 0.5 to 20 mass% of the entire basic aqueous solution, and the temperature of the basic aqueous solution during immersion is 25 to 120°C. Effect of the Invention
[0022] The present invention can provide an adhesive with excellent releasability that enables a pattern layer or the like to be easily removed from a packaging material to easily recover the sealant substrate, a packaging material comprising the adhesive, and a method for producing a recycled substrate from the packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The adhesive of the present invention is an adhesive used to form a removable adhesive layer for recycling sealant substrate 2 by peeling off substrate 1 from a packaging material having a configuration in which substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer, and sealant substrate 2 are laminated in this order from the outside, and is characterized in that it contains a polyester polyol component and at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and aralkyl polyisocyanates, and has an acid value of 5 to 40 mgKOH / g. In this adhesive, the ester bond derived from the polyol and the aliphatic structure derived from the polyisocyanate improve the affinity with an alkaline aqueous solution, so that the base material 1 and the base material 2 can be easily peeled off in an alkaline aqueous solution. When the adhesive has an acid value of 5 mgKOH / g or more, the acid value neutralizes the alkali, making it easy to peel substrate 1 and substrate 2 in an alkaline aqueous solution. When the acid value is 40 mgKOH / g or less, the adhesion and water resistance between substrate 1 and substrate 2 are good. As a result, the adhesive exhibits excellent releasability and the sealant substrate can be recovered while maintaining the adhesive strength and retort resistance required of a laminating adhesive. The present invention will be described in detail below, but these are merely examples of the embodiments of the present invention, and the present invention is not limited to these details as long as it does not depart from the gist of the present invention.
[0024] <Removable adhesive layer> The adhesive of the present invention is used to form a removable adhesive layer. "Removal" refers to the adhesive layer being removed from the sealant substrate 2 by neutralization, dissolution, etc. with a basic aqueous solution, and includes both cases: (1) the removable adhesive layer is dissolved, causing the sealant substrate 2 to peel off from the substrate 1, and (2) the adhesive layer is removed from the sealant substrate 2 by neutralization, dissolution, etc. Since the present invention aims to obtain the sealant substrate 2 after detachment as a recycled substrate or regenerated substrate, a preferred embodiment is one in which as much of the adhesive layer and substrate 1 as possible are removed from the sealant substrate 2. Specifically, it is preferred that at least 50% by mass or more of the removable adhesive layer (100% by mass) has been detached in terms of area or thickness direction. More preferred is an embodiment in which 60% by mass or more, even more preferred is 80% by mass or more, and particularly preferred is 90% by mass or more has been detached.
[0025] The basic compound used in the basic aqueous solution is not particularly limited, and examples of the basic compound that can be used include, but are not limited to, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3). More preferably, the basic compound is at least one selected from the group consisting of sodium hydroxide and potassium hydroxide.
[0026] The mechanism of detachment is assumed to be that in a packaging material containing a removable adhesive layer (for example, in an embodiment such as plastic layer / pattern layer / removable adhesive layer / sealant substrate 2), a basic aqueous solution penetrates through gaps between layers and comes into contact with the removable adhesive layer, causing the adhesive layer to dissolve and become detached from substrate 2. Therefore, the detachment step is preferably carried out in a state in which the packaging material has been cut and the cross section has been exposed, i.e., in a state in which the removable adhesive layer has been exposed.
[0027] <Adhesive> The adhesive of the present invention that forms a removable adhesive layer is characterized in that it contains a polyester polyol component and at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates, and has an acid value of 5 to 40 mgKOH / g.
[0028] [Polyester polyol component] The polyester polyol component can be selected from conventionally known polyester polyols, and may be used alone or in combination of two or more kinds. The polyester polyol component is not limited to the following, but may be, for example, a dibasic acid such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, itaconic anhydride, or a dialkyl ester thereof, or a mixture thereof (hereinafter also referred to as a carboxyl group component); For example, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, butylene glycol, neopentyl glycol, dineopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, 1,9-nonanediol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, or other diols or mixtures thereof (hereinafter also referred to as hydroxyl group components), or polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone). The above carboxyl group components and hydroxyl group components may be used in combination of two or more kinds.
[0029] The polyester polyol component may be a polyester polyurethane polyol reacted with a diisocyanate, or may be one further reacted with an acid anhydride. Examples of diisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, trimellitic ester anhydride, etc. Examples of the trimellitic ester anhydride include ethylene glycol bisanhydrotrimellitate, propylene glycol bisanhydrotrimellitate, etc.
[0030] Among them, the polyester polyol component preferably contains an acid anhydride modified polyester polyurethane polyol. The polyester polyol component has a urethane bond, and thus can exhibit excellent heat resistance and adhesiveness. When the polyester polyol component is an acid anhydride modified polyester polyol component, it is possible to finely control the acid value, and it is preferable to easily obtain a polyester polyol component having a suitable acid value range as described below.
[0031] Since the adhesive of the present invention has an acid value of 5 to 40 mgKOH / g, it is preferable that the polyester polyol component has an acid value, and the acid value of the polyester polyol component is preferably 8 mgKOH / g or more, more preferably 10 mgKOH / g or more. The acid value of the polyester polyol component is preferably 40 mgKOH / g or less. When the polyester polyol component has the above acid value, the adhesive layer formed from the adhesive of the present invention containing the polyester polyol component exhibits excellent releasability while maintaining adhesive strength, and is optimal for recycling sealant substrates from packaging materials.
[0032] When the polyester polyol component contains a plurality of polyester polyols, the acid value of the polyester polyol component can be determined from the acid value of each polyester polyol and the mass ratio thereof.
[0033] The polyester polyol component preferably has a number average molecular weight (Mn) of 3,000 to 20,000, more preferably 5,000 to 15,000, and particularly preferably 7,000 to 12,000, from the standpoint of heat sterilization resistance of the adhesive layer and coatability. When the number average molecular weight (Mn) of the polyester polyol component is 3,000 or more, not only the coatability but also sufficient retort suitability can be exhibited, and when it is 20,000 or less, not only the coatability but also the release property is improved, which is preferable.
[0034] In order to satisfy various physical properties required for the packaging material, a plurality of polyester polyols may be used in combination as the polyester polyol component. When the polyester polyol component contains a plurality of polyester polyols, the number average molecular weight of the polyester polyol component can be determined from the number average molecular weights of the respective polyester polyols and their mass ratios. The number average molecular weight in this specification is a value calculated in terms of standard polystyrene using a GPC (gel permeation chromatography) "Shodex GPC System-21" manufactured by Showa Denko KK and tetrahydrofuran as a solvent.
[0035] The polyester polyol component preferably contains a polyester polyol having a number average molecular weight of 5,000 to 15,000, and further preferably contains a polyester polyol having a number average molecular weight of less than 3,000 in order to improve adhesion to the substrate. The content of the polyester polyol having a number average molecular weight of less than 3,000 is preferably 0 to 30% by mass, and more preferably 0 to 20% by mass, based on the total amount of the polyester polyol component. When it is 30% by mass or less, retort resistance is not reduced, which is preferable.
[0036] From the viewpoints of adhesive performance and releasability, the polyester polyol component may contain the following three types of polyol components. First polyol component: polyester polyol having an acid value of 10 mg / KOH or more Second polyol component: polyester polyol having a number average molecular weight of less than 3,000 Third polyol component: polyester polyol having a number average molecular weight of 5,000 or more (However, this does not include the case where the second polyol component and the third polyol component are the first polyol component.)
[0037] The first polyol component has the role of imparting releasability, the second polyol component improves substrate adhesion and contributes to improved coatability, and the third polyol component has the role of improving retort properties. The content of the first polyol component is preferably 50% by mass or more based on the total amount of the polyester polyol component in order to exhibit sufficient releasability. The first polyol component is preferably a polyester polyurethane polyol modified with an acid anhydride, and more preferably has a number average molecular weight of 5,000 to 10,000 and an acid value of 15 mgKOH / g to 40 mgKOH / g. The second polyol component preferably has an acid value of 5 mg KOH / g or less, more preferably 1 mg KOH / g or less. The third polyol component is preferably a polyester polyurethane polyol modified with an acid anhydride, and more preferably has a number average molecular weight of 5,000 or more and 10,000 or less, and an acid value of 5 mgKOH / g or less.
[0038] (Other polyols) The adhesive of the present invention may contain other polyols besides the polyester polyol component. The polyols that may be contained other than the polyester polyol component are not particularly limited, and examples thereof include polycarbonate polyols, polycaprolactone polyols, polyether polyols, polyolefin polyols, acrylic polyols, silicone polyols, castor oil-based polyols, and fluorine-based polyols. These may be used alone or in combination of two or more kinds.
[0039] [Polyisocyanate component] The adhesive of the present invention contains at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates as a polyisocyanate component. The polyisocyanate component can be selected from conventionally known aliphatic polyisocyanates and araliphatic polyisocyanates, and two or more of them may be used in combination.
[0040] (Aliphatic polyisocyanate) The aliphatic polyisocyanate is not limited to the following, but may be a compound derived from a well-known aliphatic diisocyanate or alicyclic diisocyanate. Examples of aliphatic polyisocyanates that can be used in the present invention include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and 2,6-diisocyanate methyl caproate; Alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (hereinafter referred to as isophorone diisocyanate), 4,4'-methylenebis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanatemethyl)cyclohexane, and 1,3-bis(isocyanatemethyl)cyclohexane; Alternatively, polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above-mentioned aliphatic diisocyanates or alicyclic diisocyanates, or complexes thereof; and the like. The aliphatic polyisocyanate is preferably a polyisocyanate derived from hexamethylene diisocyanate (hereinafter also referred to as HDI), which is easy to ensure a balance of laminate properties.
[0041] (Aromatic aliphatic polyisocyanate) The araliphatic polyisocyanate is not limited to the following, but a compound derived from a well-known araliphatic diisocyanate can be used. The aromatic aliphatic polyisocyanates that can be used in the present invention include aromatic aliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof; Alternatively, polyisocyanates such as derivatives of the above-mentioned araliphatic diisocyanates or complexes thereof may be used.
[0042] (Other polyisocyanate components) The adhesive of the present invention may contain other polyisocyanates in addition to the above-mentioned aliphatic polyisocyanates and araliphatic polyisocyanates. Examples of other polyisocyanates include aromatic diisocyanates such as toluene diisocyanate and diphenylmethane diisocyanate, and polyisocyanates such as derivatives of the above-mentioned diisocyanates or complexes thereof.
[0043] [Other ingredients] The adhesive of the present invention may contain other components in addition to the polyester polyol component and at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates. The other components may be mixed with either the polyester polyol component or the polyisocyanate component, or may be added when the polyol component and the polyisocyanate component are mixed.
[0044] (Silane coupling agent) The adhesive of the present invention may further contain a silane coupling agent in order to enhance hot water resistance. Examples of the silane coupling agent include trialkoxysilanes having a vinyl group, such as vinyltrimethoxysilane and vinyltriethoxysilane, trialkoxysilanes having an amino group, such as 3-aminopropyltriethoxysilane and N-(2-aminoethyl)3-aminopropyltrimethoxysilane, and trialkoxysilanes having a glycidyl group, such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. The amount of the silane coupling agent added is preferably 0.1 to 5 mass% based on the solid content of the adhesive, and more preferably 0.5 to 3 mass%.
[0045] (Phosphorus oxygen acid or its derivatives) The adhesive of the present invention may further contain a phosphorus oxyacid or a derivative thereof in order to enhance acid resistance. Among the phosphorus oxyacids or derivatives thereof, the phosphorus oxyacid may be any one having at least one free oxyacid, and examples thereof include phosphoric acids such as hypophosphorous acid, phosphorous acid, orthophosphoric acid, and hypophosphoric acid, and condensed phosphoric acids such as metaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, polyphosphoric acid, and ultraphosphoric acid. In addition, examples of derivatives of phosphorus oxyacids include those partially esterified with alcohols in a state in which at least one free oxyacid remains. Examples of these alcohols include aliphatic alcohols such as methanol, ethanol, ethylene glycol, and glycerin, and aromatic alcohols such as phenol, xylenol, hydroquinone, catechol, and phloroglucinol. Two or more types of phosphorus oxyacids or derivatives thereof may be used in combination. The amount of phosphorus oxyacid or its derivative added is preferably 0.01 to 10 mass %, more preferably 0.05 to 5 mass %, and particularly preferably 0.1 to 1 mass %, based on the solid content of the adhesive.
[0046] The adhesive of the present invention may contain the above-mentioned phosphorus oxyacid or a derivative thereof in order to improve releasability and increase the recyclability of the sealant substrate. From the viewpoint of the strength and releasability of the packaging material, the content of the phosphorus oxyacid or a derivative thereof is preferably 0.01 to 5 mass% based on the solid content of the adhesive. More specifically, the amount of phosphorus oxyacid is more preferably 0.01 to 1 mass% based on the solid content of the adhesive, and even more preferably 0.01 to 0.5 mass%. When the amount is 0.01 mass% or more, the strength of the packaging material is maintained while the releasability is improved. When the amount is 1 mass% or less, the strength of the packaging material is excellent. The amount of the phosphoric acid derivative is preferably 0.01 to 5 mass %, more preferably 0.1 to 3 mass %, based on the solid content of the adhesive. When the amount is 0.01 mass % or more, the strength of the packaging material is maintained while the releasability is improved. When the amount is 5 mass % or less, the strength as a packaging material is excellent.
[0047] (Leveling agent or defoamer) The adhesive of the present invention may further contain a leveling agent or an antifoaming agent in order to improve the appearance of the laminate. Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane, aralkyl-modified polymethylalkylsiloxane, polyester-modified hydroxyl-containing polydimethylsiloxane, polyetherester-modified hydroxyl-containing polydimethylsiloxane, acrylic copolymer, methacrylic copolymer, polyether-modified polymethylalkylsiloxane, acrylic acid alkyl ester copolymer, methacrylic acid alkyl ester copolymer, and lecithin. Examples of the defoaming agent include known ones such as silicone resin, silicone solution, and copolymers of alkyl vinyl ether, alkyl acrylate, and alkyl methacrylate.
[0048] (Reaction accelerator) The adhesive of the present invention may further contain a reaction accelerator to promote the urethanization reaction. Examples of the reaction accelerator include metal catalysts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dimaleate; tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and 6-dibutylamino-1,8-diazabicyclo(5,4,0)undecene-7; and reactive tertiary amines such as triethanolamine. One or more reaction accelerators selected from these groups may be used.
[0049] The adhesive of the present invention may contain various additives within a range that does not impair the effects of the present invention. Examples of additives include inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, and glass flakes, layered inorganic compounds, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, hydrolysis inhibitors, etc.), rust inhibitors, thickeners, plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, fillers, crystal nucleating agents, and catalysts for adjusting the curing reaction.
[0050] In addition, the adhesive of the present invention can contain fine particles having an average particle size of 1 to 10 μm as the above-mentioned additive in order to improve releasability and increase the recyclability of the sealant substrate. It is presumed that the inclusion of such fine particles maintains the strength of the packaging material due to an anchoring effect on the substrate, while reducing the contact area between the adhesive and the substrate, thereby improving releasability. When the average particle size is 1 μm or more, the strength of the packaging material is maintained while improving the release property. When the average particle size is 10 μm or less, the strength of the packaging material can be maintained. In this specification, the average particle size means the median size measured by a particle size distribution measuring device using a laser diffraction / scattering method. The fine particles having an average particle size of 1 to 10 μm are not particularly limited, and examples thereof include inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, and glass flakes, as well as aluminum hydroxide, precipitated barium sulfate, magnesium carbonate, calcium carbonate, zeolite, and resin beads such as acrylic beads and urethane beads.
[0051] From the viewpoint of the strength and releasability of the packaging material, the blending amount of the fine particles is preferably 0.1 to 10 mass % based on the solid content of the adhesive, and more preferably 0.5 to 5.0 mass %. When the blending amount is 0.5 mass % or more, the strength of the packaging material is maintained while the releasability is improved. When the blending amount is 5.0 mass % or less, the strength as a packaging material is excellent.
[0052] The adhesive of the present invention preferably contains a combination of the phosphorus oxygen acid or derivative thereof and the fine particles having an average particle size of 1 to 10 μm. By using the above in combination, the releasability and removal rate are further improved.
[0053] The adhesive of the present invention can be used as a solventless type when its viscosity is 100 to 10,000 mPa·s, preferably 100 to 5,000 mPa·s at room temperature to 150°C, preferably room temperature to 100°C. If the viscosity of the adhesive is higher than the above range, it may be diluted with an organic solvent. As the organic solvent, for example, esters such as ethyl acetate, ketones such as methyl ethyl ketone, aromatic hydrocarbons such as toluene and xylene, etc., which are inactive to the polyisocyanate component, are suitably used, and can be appropriately selected and used.
[0054] The adhesive of the present invention is a two-liquid curing urethane adhesive containing a polyester polyol component and a polyisocyanate component, and has an acid value immediately after mixing of 5 mgKOH / g or more, more preferably 7 mgKOH / g or more, and particularly preferably 10 mgKOH / g or more. Also, the acid value of the adhesive of the present invention immediately after mixing is 40 mgKOH / g or less, preferably 30 mgKOH / g or less, and more preferably 20 mgKOH / g or less.
[0055] When the polyester polyol component and the polyisocyanate component are mixed, they are mixed so that the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyol is 0.3 to 5.0, more preferably 0.3 to 2.0, and particularly preferably 0.5 to 1.5.
[0056] The removable adhesive layer is formed from the adhesive of the present invention. A typical method for forming the adhesive layer is to apply an adhesive to one side of a substrate 1 having a plastic layer and a pattern layer, and then, if necessary, to a drying step to volatilize the organic solvent, to bond the adhesive to one side of a sealant substrate 2 using a laminator, and to harden the adhesive at room temperature or under heating to form a removable adhesive layer. The sealant substrate 2 may be a layer formed by extrusion lamination. Examples of a method for laminating the sealant substrate 2 by extrusion lamination include a method in which an adhesive is applied to one side of a substrate 1 having a plastic layer and a pattern layer, and an organic solvent is evaporated through a drying process as necessary, and then a molten sealant resin is extruded by a T-die method, the sealant substrate 2 is laminated by a cooling roll, and the sealant substrate 2 is cured at room temperature or under heating to form a removable adhesive layer. The amount of adhesive applied after drying is optional, but is usually 0.001 to 6 g / m 2 In the case of the solventless type, the range is preferably 1 to 2 g / m 2 , 1-6g / m for solvent-based 2 The range is. In addition, when the sealant base material 2 is a layer formed by extrusion lamination, the coating amount of the adhesive after drying is preferably 0.01 to 1 g / m 2 More preferably, it is in the range of 0.05 to 0.5 g / m 2 The range is.
[0057] <Packaging material> The packaging material of the present invention has a configuration in which a substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer formed from the adhesive of the present invention, and a sealant substrate 2 are laminated in this order from the outside, with the removable adhesive layer being provided in contact with the substrate 1, and the sealant substrate 2 being provided on the side of the removable adhesive layer opposite the substrate 1. The thickness of the removable adhesive layer can be adjusted appropriately depending on the type of adhesive and the sealant substrate 2, but is preferably 1 to 10 μm, and more preferably 1 to 6 μm. In particular, when the sealant substrate 2 is a layer formed by extrusion lamination, the thickness of the removable adhesive layer is preferably 0.01 to 1 μm, and more preferably 0.05 to 0.5 μm.
[0058] [Base material 1] The substrate 1 is preferably in the form of a film having at least a plastic layer and a pattern layer among the multiple layers constituting the substrate 1. The thickness of the substrate 1 is preferably 5 to 200 μm, more preferably 10 to 100 μm.
[0059] (Plastic layer) Examples of the plastic layer include those generally used in packaging materials, such as polyester resin films such as polyethylene terephthalate, polyethylene naphthalate (PEN), and polylactic acid (PLA); polyolefin resin films such as polyethylene (PE) and polypropylene (PP); polystyrene resin films; polyamide resin films such as nylon 6 and poly-p-xylylene adipamide (MXD6 nylon); polycarbonate resin films; polyacrylonitrile resin films; polyimide resin films; laminates thereof (e.g., nylon 6 / MXD6 / nylon 6, nylon 6 / ethylene-vinyl alcohol copolymer / nylon 6) and mixtures thereof. Among these, those having mechanical strength and dimensional stability are preferred. The plastic layer preferably has a thickness of 5 μm or more and 50 μm or less, more preferably 10 μm or more and 30 μm or less.
[0060] (Picture layer) The design layer is a layer on which any desired printed pattern such as letters, numbers, pictures, figures, symbols, patterns, etc. is formed for decoration, display of contents, display of expiration date, display of manufacturer, seller, etc., or for imparting aesthetic appeal, and also includes a solid print layer. The design layer can be formed using conventionally known pigments or dyes, and the method for forming the design layer is not particularly limited. In general, the design layer is formed using a printing ink containing a colorant such as a pigment or dye. The method for applying the printing ink is not particularly limited, and the printing ink can be applied by a method such as gravure coating, flexo coating, roll coating, bar coating, die coating, curtain coating, spin coating, inkjet, etc. The printing layer can be formed by leaving the ink alone or, if necessary, blowing air, heating, drying under reduced pressure, irradiating with ultraviolet light, etc. The design layer preferably has a thickness of 0.1 μm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less, and further preferably 1 μm or more and 3 μm or less.
[0061] In addition to the plastic layer and the design layer, the substrate 1 may further comprise another layer, which may be provided either between the plastic layer and the design layer, on the plastic layer or on the design layer. Other layers that may be present between the plastic layer and the design layer include, for example, a base layer or an anchor layer. Other layers that may be present on the plastic layer or on the design layer include the above-mentioned plastic layer, paper, or a gas barrier layer such as a metal foil or a vapor deposition layer. These other layers may be formed in multiples, and may be laminated via an adhesive layer. The paper includes natural paper and synthetic paper. Examples of the gas barrier layer include aluminum foil, as well as vapor-deposited layers of aluminum, silica, alumina, etc. For example, in the case of aluminum foil, a thickness in the range of 3 to 50 μm is preferable from an economical point of view. As the adhesive layer for laminating another layer, either a known adhesive or the adhesive of the present invention may be used.
[0062] [Sealant base material 2] Examples of the sealant base material 2 include polyethylenes such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and high-density polyethylene (HDPE), acid-modified polyethylene, polypropylene (PP), acid-modified polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-(meth)acrylic acid copolymer, and ionomer. From the viewpoint of recyclability, polyethylenes such as low-density polyethylene, linear low-density polyethylene and high-density polyethylene, acid-modified polyethylene, polypropylene, acid-modified polypropylene, copolymer polypropylene and other polyolefin resins are preferred. From the viewpoint of heat resistance during retort, polypropylene-based resins are preferred, and from the viewpoint of heat sealability, unstretched polypropylene is particularly preferred. The thickness of the sealant base material 2 is not particularly limited, but is preferably 10 to 150 μm, and more preferably 20 to 70 μm, in consideration of processability into packaging materials, heat sealability, etc. Furthermore, by providing the sealant base material 2 with unevenness having a height difference of about several μm, it is possible to impart slipperiness and tearability to the packaging material. The method for laminating the sealant substrate is not particularly limited, and examples thereof include a method in which the substrate 1 and the sealant substrate 2 are thermally laminated using the adhesive of the present invention (thermal lamination, dry lamination), and a method in which a sealant resin is melted and extruded onto an adhesive layer using the adhesive of the present invention, and then cooled and solidified to form the sealant substrate 2 (extrusion lamination method).
[0063] Examples of the configuration of the packaging material of the present invention are given below, but the present invention is not limited to these. Biaxially oriented polypropylene (OPP) / pattern layer / removable adhesive layer / non-oriented polypropylene (CPP), OPP / Pattern layer / Removable adhesive layer / Al vapor-deposited CPP, OPP / Pattern layer / Removable adhesive layer / PE, Pattern layer / OPP / Removable adhesive layer / CPP, NY / pattern layer / removable adhesive layer / PE, Pattern layer / NY / Removable adhesive layer / CPP NY / pattern layer / removable adhesive layer / CPP, PET / Pattern layer / Removable adhesive layer / CPP, Pattern layer / PET / Removable adhesive layer / CPP PET / Pattern layer / Adhesive layer / NY / Removable adhesive layer / CPP, Transparent vapor deposition PET / Pattern layer / Adhesive layer / NY / Removable adhesive layer / CPP, PET / Pattern layer / Adhesive layer / AL / Removable adhesive layer / CPP, PET / Pattern layer / Adhesive layer / AL / Removable adhesive layer / PE, PET / Pattern layer / Adhesive layer / NY / Adhesive layer / AL / Removable adhesive layer / CPP, PET / pattern layer / adhesive layer / AL / adhesive layer / NY / removable adhesive layer / CPP.
[0064] <Recycled substrate manufacturing method> The method for producing a recycled substrate of the present invention includes a step of immersing a packaging material having a structure in which a substrate 1 having a plastic layer and a design layer, a removable adhesive layer, and a sealant substrate 2 are laminated in this order from the outside, in a basic aqueous solution. More specifically, the method for producing a recycled substrate of the present invention includes a step of immersing the packaging material in a basic aqueous solution, and a step of peeling the substrate 1 having the plastic layer and the design layer from the packaging material to recover the sealant substrate 2.
[0065] The basic aqueous solution preferably contains a basic compound in an amount of 0.5 to 20 mass % of the entire basic aqueous solution, more preferably 1 to 15 mass %, and particularly preferably 3 to 15 mass %. When the concentration is within the above range, the basic aqueous solution can retain sufficient basicity to dissolve or swell the removable adhesive and remove it, thereby peeling off the substrate 1. The basic aqueous solution penetrates the edge of the packaging material, comes into contact with the removable adhesive layer, and dissolves or swells it, separating substrate 1 from substrate 2. Therefore, in order to efficiently proceed with the removal process, it is preferable that the packaging material is cut or crushed so that the removable adhesive layer is exposed on the cross section when it is immersed in the basic aqueous solution. In such a case, the picture ink layer, substrate, etc. can be removed in a shorter time.
[0066] The temperature of the basic aqueous solution when the packaging material is immersed is preferably 25 to 120°C, more preferably 30 to 120°C, and particularly preferably 30 to 80°C. The immersion time in the basic aqueous solution is preferably 1 minute to 24 hours, more preferably 1 minute to 12 hours, and preferably 1 minute to 6 hours. The amount of the basic aqueous solution used is preferably 100 to 1,000,000 times the mass of the packaging material, and in order to improve the desorption efficiency, it is preferable to stir or circulate the basic aqueous solution. The rotation speed is preferably 80 to 250 rpm, and more preferably 80 to 200 rpm.
[0067] The substrate 1 having a plastic layer and a pattern layer is peeled off from the packaging material to recover the sealant substrate 2, which is then subjected to a process of rinsing with water and drying to obtain a recycled substrate. The removal rate of the removable adhesive layer on the surface of the sealant substrate 2 is preferably 40% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more, of 100% by mass of the removable adhesive layer.
[0068] Therefore, according to the present invention, a recycled base material of the sealant base material can be obtained through the steps of immersing the packaging material in a basic aqueous solution, removing the adhesive layer, peeling the base material 1 having the plastic layer and the pattern layer from the packaging material to recover the sealant base material 2, and washing and drying the sealant base material 2. The obtained recycled base material can be processed into pellets using an extruder or the like and reused as recycled resin. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples and comparative examples. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.
[0070] <Acid value measurement> Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and dissolved in 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture. Phenolphthalein test solution was added as an indicator and held for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) F: Factor of 0.1N alcoholic potassium hydroxide solution
[0071] <Number average molecular weight (Mn)> The number average molecular weight (Mn) was measured using a GPC (gel permeation chromatography) "Shodex GPC System-21" manufactured by Showa Denko KK In the measurement, tetrahydrofuran was used as a solvent, and the value was calculated in terms of standard polystyrene.
[0072] <Production of polyol> (Production Example 1) Polyester polyol (P-1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 263 parts of ethylene glycol, 468 parts of neopentyl glycol, 472 parts of isophthalic acid and 528 parts of adipic acid were charged, and the temperature was raised to 250°C while stirring under a nitrogen stream. After the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced, and the deglycolization reaction was carried out at 1 mmHg for 5 hours to obtain a polyester polyol. Next, the solution was diluted with ethyl acetate until the nonvolatile content was 50%, and a solution of polyester polyol (P-1) with a number average molecular weight of 2,500 and an acid value of 0.5 mgKOH / g was obtained.
[0073] (Production Example 2) Polyester polyol (P-2) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 236 parts of ethylene glycol, 263 parts of neopentyl glycol, 202 parts of 1,6-hexanediol, 82 parts of terephthalic acid, 682 parts of isophthalic acid and 236 parts of adipic acid were charged, and the temperature was raised to 250 ° C. while stirring under a nitrogen stream. After continuing the reaction until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg for 5 hours to obtain a polyester polyol. Then, 2 parts of isophorone diisocyanate were gradually added, and the reaction was carried out at 150 ° C. for about 2 hours to obtain a polyester polyurethane polyol. 2.5 parts of trimellitic anhydride were added to 100 parts of this polyester polyurethane polyol, and the reaction was carried out at 180 ° C. for about 2 hours, and then the mixture was diluted with ethyl acetate until the non-volatile content was 50%, thereby obtaining a solution of a partially acid-modified polyester polyol (P-2) having a number average molecular weight of 6,000 and an acid value of 14.5 mg KOH / g.
[0074] (Production Example 3) Polyester polyol (P-3) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 202 parts of ethylene glycol, 331 parts of 2-methyl-1,3-propanediol, 77 parts of 1,6-hexanediol, 262 parts of terephthalic acid, 393 parts of isophthalic acid and 345 parts of adipic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream. After the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced, and a deglycolization reaction was carried out at 1 mmHg for 5 hours to obtain a polyester polyol. Then, 2 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 0.6 parts of trimellitic anhydride was added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol (P-3) with a number average molecular weight of 7,000 and an acid value of 3.6 mgKOH / g.
[0075] (Production Example 4) Polyester polyol (P-4) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 202 parts of ethylene glycol, 253 parts of neopentyl glycol, 247 parts of 1,6-hexanediol, 682 parts of isophthalic acid, 72 parts of adipic acid and 274 parts of sebacic acid were charged and heated to 250°C while stirring under a nitrogen stream. After the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg for 5 hours to obtain a polyester polyol. Then, 20 parts of isophorone diisocyanate was gradually added and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 3.5 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol (P-4) with a number average molecular weight of 8,000 and an acid value of 9.9 mgKOH / g.
[0076] (Production Example 5) Polyester polyol (P-5) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 240 parts of ethylene glycol, 253 parts of neopentyl glycol, 247 parts of 1,6-hexanediol, 682 parts of isophthalic acid, 72 parts of adipic acid and 274 parts of sebacic acid were charged and heated to 250°C while stirring under a nitrogen stream. After the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg for 5 hours to obtain a polyester polyol. Then, 40 parts of isophorone diisocyanate was gradually added and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 13.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the non-volatile content reached 50%, yielding a solution of partially acid-modified polyester polyol (P-5) with a number average molecular weight of 9,500 and an acid value of 32.1 mg KOH / g.
[0077] (Production Example 6) Polyester polyol (P-6) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 283 parts of ethylene glycol, 468 parts of neopentyl glycol, 472 parts of isophthalic acid and 528 parts of adipic acid were charged, and the temperature was raised to 250 ° C. while stirring under a nitrogen stream. After continuing the reaction until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg for 5 hours to obtain a polyester polyol. 3.5 parts of trimellitic anhydride were added to 100 parts of this polyester polyol, and the reaction was carried out at 180 ° C. for about 2 hours, and then diluted with ethyl acetate until the non-volatile content was 50%, to obtain a solution of partially acid-modified polyester polyol (P-6) with a number average molecular weight of 2,000 and an acid value of 21.1 mg KOH / g.
[0078] (Production Example 7) Polyether polyol (P-7) 81.95 parts of P-2000 (trade name, manufactured by ADEKA Corporation, bifunctional polyoxypropylene glycol, hydroxyl value 56.1), 382.3 parts of P-400 (trade name, manufactured by ADEKA Corporation, bifunctional polyoxypropylene glycol, hydroxyl value 265.9), 81.95 parts of T-400 (trade name, manufactured by Mitsui Chemicals, Inc., trifunctional polyoxypropylene glycol, hydroxyl value 404), 19 parts of dimethylolpropionic acid, 132.91 parts of ethyl acetate, 95.53 parts of tolylene diisocyanate, and 121 parts of 4,4-diphenylmethane diisocyanate, and 0.22 parts of dibutyltin laurate were charged, heated to 90 ° C., and reacted until the peak of the isocyanate group disappeared in the infrared absorption spectrum. Next, the solution was diluted with ethyl acetate to a non-volatile content of 50%, thereby obtaining a solution of partially acid-modified polyether polyol (P-7) having a number average molecular weight of 9,000 and an acid value of 10.4 mgKOH / g.
[0079] [Table 1]
[0080] <Adjustment of polyisocyanate> (Production Example 8) Polyisocyanate (C-1) Coronate 2785 (biuret type polyisocyanate derived from hexamethylene diisocyanate, manufactured by Tosoh Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 9.6%, to obtain a solution of polyisocyanate (C-1).
[0081] (Production Example 9) Polyisocyanate (C-2) Bestanat T1890 / 100 (nurate type polyisocyanate derived from isophorone diisocyanate (hereinafter, IPDI), manufactured by Evonik Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 8.7%, to obtain a solution of polyisocyanate (C-2).
[0082] (Production Example 10) Polyisocyanate (C-3) Takenate D-110NB (trimethylolpropane adduct type polyisocyanate derived from xylylene diisocyanate (hereinafter, XDI), manufactured by Mitsui Chemicals) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 7.9%, to obtain a solution of polyisocyanate (C-3).
[0083] (Production Example 11) Polyisocyanate (C-4) Coronate L (a trimethylolpropane adduct type polyisocyanate derived from toluene diisocyanate (hereinafter, TDI), manufactured by Tosoh Corporation) was diluted with ethyl acetate to adjust the non-volatile content to 50% and NCO% to 8.8%, to obtain a solution of polyisocyanate (C-4).
[0084] (Production Example 12) Polyisocyanate (C-5) Millionate MR-200 (a polymeric polyisocyanate derived from diphenylmethane diisocyanate (hereinafter, MDI), manufactured by Tosoh Corporation) was diluted with ethyl acetate and adjusted to a non-volatile content of 50% and NCO% of 8.8%, to obtain a solution of polyisocyanate (C-5).
[0085] <Adhesive manufacturing> [Examples 1 to 23, Comparative Examples 1 to 6] The polyol solutions and polyisocyanate solutions obtained in Production Examples 1 to 12 above were mixed in the ratios (mass ratios) shown in Tables 2 and 3, and ethyl acetate was added to prepare adhesive solutions with a non-volatile content of 30%.
[0086] [Examples 24 to 26] The polyol solutions and polyisocyanate solutions obtained in the above Production Examples 1 to 3, 5, 6, and 8 were mixed in the ratios (mass ratios) shown in Table 4, and ethyl acetate was added to prepare adhesive solutions with a non-volatile content of 13%.
[0087] <Adhesive evaluation> Using the obtained adhesive solution, packaging materials 1 to 3 were produced by the following method. The obtained packaging materials were subjected to adhesive strength and releasability tests as described below. The results are shown in Tables 2 to 4.
[0088] (Manufacturing of packaging material 1) Printing inks (Toyo Ink Co., Ltd., Rio Alpha R39 indigo, R631 white) were each diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). Each diluted printing ink was printed in the order of indigo and white on a corona-treated PET film (thickness 12 μm) using a gravure proofing two-color machine equipped with a solid plate with a plate depth of 35 μm. The printing speed was 50 m / min, and drying was performed at 50°C in each unit to obtain a PET / design layer laminate. The design layer had a thickness of 1 μm. Next, an adhesive (TM-250HV / CAT-RT86L-60, manufactured by Toyo-Morton Co., Ltd.) was applied to the pattern layer of the obtained laminate using a laminator, and the solvent was evaporated, and then the applied surface was laminated to a nylon film having a thickness of 15 μm. The thickness of the adhesive layer was 3 μm. Next, the adhesives obtained in the Examples and Comparative Examples were applied to the nylon film surface of the obtained laminate in the same manner as above, and after the solvent was evaporated, the applied surface was laminated to a 70 μm-thick CPP film that had been surface-treated with corona discharge. The thickness of the removable adhesive layer was 3 μm. The obtained laminate was then kept at 40°C for 4 days to obtain a packaging material having a structure of PET (12 μm) / design layer (1 μm) / adhesive layer (3 μm) / NY (15 μm) / detachable adhesive layer (3 μm) / CPP (70 μm).
[0089] (Manufacturing of packaging material 2) Printing inks (Toyo Ink Co., Ltd., Rio Alpha R39 indigo, R631 white) were each diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). Each diluted printing ink was printed in the order of indigo and white on a corona-treated OPP film (thickness 20 μm) using a gravure proofing two-color machine equipped with a solid plate with a plate depth of 35 μm. The printing speed was 50 m / min, and drying was performed at 50°C in each unit to obtain an OPP / design layer laminate. The design layer had a thickness of 1 μm. Next, the adhesive obtained in the Examples and Comparative Examples was applied to the pattern layer of the obtained laminate using a laminator, the solvent was evaporated, and then the coated surface was laminated to a 25 μm thick CPP film that had been surface-corona discharge-treated. The resulting laminate was then kept at 40° C. for 4 days to obtain a packaging material having a structure of OPP (20 μm) / picture layer (1 μm) / removable adhesive layer (2 μm) / CPP (25 μm).
[0090] (Production of packaging material 3) Printing inks (Toyo Ink Co., Ltd., Rio Alpha R39 indigo, R631 white) were each diluted with an ethyl acetate / IPA mixed solvent (mass ratio 70 / 30) so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). Each diluted printing ink was printed in the order of indigo and white on a corona-treated PET film (PET) with a thickness of 12 μm using a gravure proofing two-color machine equipped with a solid plate with a plate depth of 35 μm. The printing speed was 50 m / min, and drying was performed at 50°C in each unit to obtain a PET / design layer laminate. The design layer had a thickness of 1 μm. Next, the obtained laminate was sent out from the first roll, and the adhesive obtained in the Example was applied onto the design layer using a gravure coater, the solvent was evaporated, and a removable adhesive layer having a thickness of 0.3 μm was formed. Then, the laminate was extruded from a T-die using extrusion polyethylene (LDPE EXT ) was extruded at 315°C, cooled on a cooling roll and wound up. The resulting laminate was then kept at 40°C for 4 days to form a laminate of PET (12 µm) / pattern layer (1 µm) / removable adhesive layer (0.3 µm) / LDPE. EXT A packaging material having a structure of (30 μm) was obtained.
[0091] <Evaluation of packaging material 1> (Adhesive strength before retort) Test pieces measuring 15 mm × 300 mm were prepared from packaging material 1, and the laminate strength (N / 15 mm) between NY and CPP was measured using a tensile tester under conditions of a temperature of 20°C and a relative humidity of 65% using a T-type peel at a peel speed of 30 cm / min.
[0092] (Adhesive strength after retort) A pouch measuring 21 cm × 30 cm was prepared using the packaging material 1, and a sauce containing salad oil, ketchup, and 4.2% vinegar in a mass ratio of 1:1:1 was vacuum-filled as the content. The obtained pouch was sterilized with hot water at 10 rpm, 120°C, 30 minutes, and a pressure of 3 MPa. Test pieces measuring 15 mm x 300 mm were prepared from the pouches that had been subjected to the above-mentioned retort treatment, and the laminate strength (N / 15 mm) between NY and CPP was measured in the same manner as the adhesive strength before retort.
[0093] (Releasability) Three test pieces measuring 2.0 cm x 2.0 cm were cut out from the pouch after the retort treatment, and were immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C at a rotation speed of 100 rpm. The time it took for the NY and CPP to peel off was measured, and the results were evaluated according to the following criteria. ◎: All separation between NY and CPP occurred within 20 minutes (very good) ○: All NY and CPP peeled off within 20 minutes to 1 hour (good) △: The NY and CPP are completely peeled off within 1 to 12 hours (usable) ×: No peeling between NY and CPP occurred within 12 hours (unusable)
[0094] (removal rate) A test piece measuring 2.0 cm x 2.0 cm was cut out from the pouch after the retort treatment, and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C for 1 hour at a rotation speed of 100 rpm to peel the NY and CPP apart. After that, the piece was washed with water and dried to obtain a recycled CPP film measuring 2.0 cm x 2.0 cm. The recycled CPP film obtained was checked for the presence or absence of an absorption peak of the adhesive at five locations, the four edges and the center, on the surface where the removable adhesive layer was in contact, using FT-IR, and was evaluated according to the following criteria. Films in which the NY and CPP did not peel within one hour were deemed unsatisfactory. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)
[0095] <Evaluation of packaging material 2> (Adhesive strength) Test pieces measuring 15 mm x 300 mm were prepared from packaging material 2, and the laminate strength (N / 15 mm) between the OPP and CPP was measured using a tensile tester at a temperature of 20°C and a relative humidity of 65% using a T-type peeling method at a peeling speed of 30 cm / min.
[0096] (Releasability (1)) A test piece measuring 2.0 cm x 2.0 cm was cut out from the obtained packaging material 2 and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C at a rotation speed of 100 rpm. The time it took for the OPP and CPP to peel off was measured and evaluated according to the following criteria. ◎: OPP and CPP completely peeled off within 20 minutes (very good) ○: OPP and CPP are completely peeled off within 20 minutes to 1 hour (good) △: OPP and CPP completely peel off within 1 to 12 hours (usable) ×: OPP and CPP are not completely peeled off within 12 hours (unusable)
[0097] (Releasability (2)) A test piece measuring 3.0 cm x 3.0 cm was cut out from the obtained packaging material 2 and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C at a rotation speed of 50 rpm. The time it took for the OPP and CPP to peel off was measured and evaluated according to the following criteria. ◎: OPP and CPP completely peeled off within 20 minutes (very good) ○: OPP and CPP are completely peeled off within 20 minutes to 1 hour (good) △: OPP and CPP completely peel off within 1 to 12 hours (usable) ×: OPP and CPP are not completely peeled off within 12 hours (unusable)
[0098] (Removal rate (1)) A test piece measuring 2.0 cm x 2.0 cm was cut out from the obtained packaging material 2, and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C for 1 hour at a rotation speed of 100 rpm to peel off the OPP and CPP. After that, the piece was washed with water and dried to obtain a recycled CPP film measuring 2.0 cm x 2.0 cm. The recycled CPP film obtained was checked for the presence or absence of an absorption peak of the adhesive at five locations, the four edges and the center, on the surface where the removable adhesive layer was in contact, using FT-IR, and was evaluated according to the following criteria. Films that did not peel between the OPP and CPP within 1 hour were deemed unsatisfactory. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)
[0099] (Removal rate (2)) A test piece measuring 3.0 cm x 3.0 cm was cut out of the obtained packaging material 2, and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C for 1 hour at a rotation speed of 50 rpm to peel off the OPP and CPP. After that, the piece was washed with water and dried to obtain a recycled CPP film measuring 3.0 cm x 3.0 cm. The recycled CPP film obtained was checked for the presence or absence of an absorption peak of the adhesive at five locations, the four edges and the center, on the surface where the removable adhesive layer was in contact, using FT-IR, and was evaluated according to the following criteria. Films that did not peel between the OPP and CPP within 1 hour were deemed unsatisfactory. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)
[0100] <Evaluation of packaging material 3> (Adhesive strength before boiling) A test piece measuring 15 mm x 300 mm was made from packaging material 3, and a tensile tester was used to test the PET / LDPE material at a temperature of 20°C and a relative humidity of 65% at a peel speed of 30 cm / min using a T-type peeling method. EXT The laminate strength (N / 15 mm) between the sheets was measured.
[0101] (Adhesive strength after boiling) A pouch measuring 21 cm×30 cm was prepared using the packaging material 3, and water was vacuum-filled as the content. The obtained pouch was subjected to a heat treatment at 85° C. for 30 minutes. From the pouches that had been subjected to the boiling treatment, test pieces measuring 15 mm x 300 mm were made, and the adhesive strength of the PET / LDPE was measured in the same manner as that before boiling. EXT The laminate strength (N / 15 mm) between the sheets was measured.
[0102] (Releasability) Three test pieces measuring 2.0 cm x 2.0 cm were cut out from the pouch after the boiling process, and were immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C at a rotation speed of 100 rpm. EXT The time it took for the adhesive to peel off was measured and evaluated according to the following criteria. ◎: PET and LDPE within 20 minutes EXT All areas between the adhesive and the adhesive peel off (very good) ○: PET and LDPE for 20 minutes or more and within 1 hour EXT All areas between the adhesive and the adhesive peel off (good) △: PET and LDPE within 1 to 12 hours EXT All areas between the adhesive and the adhesive are peeled off (usable) ×: Within 12 hours, PET and LDPE EXT The area between the adhesive and the adhesive does not peel off (cannot be used)
[0103] (removal rate) Test pieces measuring 2.0 cm x 2.0 cm were cut out from the pouches after the boiling process, and immersed and stirred in 50 g of a 2% aqueous solution of sodium hydroxide (NaOH) at 70°C for 1 hour at a rotation speed of 100 rpm. EXT After peeling, the film was washed with water and dried to obtain a recycled PE film measuring 2.0 cm x 2.0 cm. The recycled PE film obtained was examined for the presence or absence of an absorption peak of the adhesive at five locations, the four edges and the center, on the surface where the removable adhesive layer was in contact, using FT-IR, and was evaluated according to the following criteria. EXT If there was no peeling between the adhesive and the adhesive, the adhesive was deemed unevaluable. ◎: No adhesive absorption peak at all five locations (removal rate is approximately 100%: very good) ○: Adhesive absorption peak was observed in only one of the five locations (removal rate was about 80%: good) △: Adhesive absorption peaks in 2 to 3 of the 5 locations (removal rate is about 40 to 60%: usable) ×: Adhesive absorption peaks in 4 or more of the 5 locations (removal rate is about 20%: not usable)
[0104] [Table 2]
[0105] According to the results in Table 2, the adhesive of the present invention, which contains a polyester polyol component including an acid anhydride-modified polyester polyurethane polyol and at least one polyisocyanate component selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates, and has an acid value of 5 to 40 mgKOH / g, has retort suitability and excellent alkali release properties, and allows the sealant substrate to be easily separated from the packaging material, thereby improving the recyclability of the sealant substrate. In particular, Examples 5, 6, and 11, which used a polyester polyol with a number-average molecular weight of less than 3,000, showed excellent alkali release properties and removal rates as well as excellent laminate strength.
[0106] [Table 3]
[0107] The abbreviations in Table 3 are as follows: Phosphoric acid: 85% phosphoric acid aqueous solution Phosphoric acid derivative: Phosphanol RL-310, manufactured by Toho Chemical Industry Co., Ltd. Aluminum hydroxide 1: BF013, manufactured by Nippon Light Metal Co., Ltd., average particle size 1 μm Aluminum hydroxide 2: BX103, manufactured by Nippon Light Metal Co., Ltd., average particle size 5 μm Aluminum hydroxide 3: BF083, manufactured by Nippon Light Metal Co., Ltd., average particle size 10 μm Acrylic resin beads: Art Pearl J-7P, manufactured by Negami Chemical Industries, Ltd., average particle size 6 μm
[0108] According to the results in Table 3 above, the desorption performance was improved in Examples 12 to 16 in which phosphoric acid or a phosphoric acid derivative was added, and in Example 17 in which fine particles having an average particle size of 1 to 10 μm were added, compared to Example 11. Furthermore, Examples 18 to 23 in which both phosphoric acid and fine particles having an average particle size of 1 to 10 μm were added showed a tendency to improve the desorption performance or removal rate.
[0109] [Table 4]
[0110] According to the results in Table 4 above, the packaging material 3 in which the sealant substrate 2 was laminated by extrusion lamination had a thinner removable adhesive layer than that obtained by conventional dry lamination, but exhibited good alkali release properties and removal rate as well as excellent laminate strength.
Claims
1. A substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer, and a sealant substrate 2 are laminated in this order from the outside, and an adhesive that forms a removable adhesive layer that constitutes a packaging material in which the substrate 1 is peeled off and the sealant substrate 2 is recycled, The adhesive comprises a polyester polyol component and at least one polyisocyanate component selected from the group consisting of an aliphatic polyisocyanate and an araliphatic polyisocyanate, the araliphatic polyisocyanate being selected from the compounds listed below: <A compound selected from 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof; and a compound selected from the above-mentioned derivatives and complexes. The adhesive has an acid value of 5 to 40 mgKOH / g.
2. 2. The adhesive according to claim 1, wherein the polyester polyol component has a number average molecular weight of 5,000 to 15,000.
3. The adhesive according to claim 1 or 2, wherein the acid value of the polyester polyol component is 10 to 40 mg KOH / g.
4. The adhesive according to any one of claims 1 to 3, wherein the polyester polyol component comprises an acid anhydride modified polyester polyurethane polyol.
5. The adhesive according to any one of claims 1 to 4, wherein the polyester polyol component comprises a polyester polyol having a number average molecular weight of 5,000 to 15,000 and a polyester polyol having a number average molecular weight of less than 3,000.
6. The adhesive according to any one of claims 1 to 5, further comprising 0.01 to 5 mass% of a phosphorus oxyacid or a derivative thereof based on the solid content of the adhesive.
7. The adhesive according to any one of claims 1 to 6, further comprising fine particles having an average particle size of 1 to 10 µm.
8. The adhesive according to claim 7, wherein the content of the fine particles is 0.1 to 10 mass % based on the solid content of the adhesive.
9. A packaging material comprising a substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer formed from the adhesive according to any one of claims 1 to 8, and a sealant substrate 2 laminated in this order from the outside.
10. 10. The packaging material according to claim 9, wherein the sealant substrate (2) is a layer formed by extrusion lamination, and the removable adhesive layer has a thickness of 0.01 to 1 μm.
11. A method for producing a recycled substrate, comprising the step of immersing a packaging material in a basic aqueous solution, the packaging material comprising a substrate 1 having a plastic layer and a pattern layer, a removable adhesive layer formed from the adhesive according to any one of claims 1 to 8, and a sealant substrate 2, laminated in this order from the outside; The basic aqueous solution contains a basic compound in an amount of 0.5 to 20% by mass based on the total amount of the basic aqueous solution, and the temperature of the basic aqueous solution during immersion is 25 to 120° C.
Citation Information
Patent Citations
Ink composition having elimination performance and method for eliminating ink composition from print
JP1999209677A
Article having releasable surface layer, releasable surface layer-forming material, method for releasing and removing surface layer from article, and article having removed surface layer therefrom
JP2001131484A
Heat sensitive tacky agent composition and heat sensitive tacky sheet
JP2001207151A
Latent hydrophilic resin and composition containing the resin
JP2001261746A
Washable PSA laminate
JP2012501829A